ISOLASI DAN IDENTIFIKASI SENYAWA ALKALOID BUAH MAHKOTA DEWA (Phaleria macrocarpa (Scheff.) Boerl) SECARA SPEKTROFOTOMETRI UV-Vis DAN IR SERTA UJI TOKSISITAS AKUT TERHADAP LARVA Artemia salina Leach - Christina Astutiningsih; Frida Nuzulia; Agus Suprijono (Jurnal Farmasi Sains dan Komunitas (Journal of Pharmaceutical Sciences and Community), 2012)
Abstract: Fruit Mahkota Dewa (Phaleria macrocarpa (Scheff.) Boerl) contains alkaloid, tannin,saponin, flavonoid, terpenoid dan lignin. The aim of this study was to elucidate compound fromMahkota Dewa based on the analyses on spectrophotometry UV-Vis, IR and to evaluate thecompound in the Brine Shrimp Lethality Test. On IR spectra revealed the presence of alkaloidamin primer. The isolated alkaloid compound was found to be toxic to brine shrimp with LC5033.8932 ?g/ml.Keywords: alkaloid, Mahkota Dewa, toxicity, Artemia salina Leach